2008
DOI: 10.1037/0735-7036.122.3.235
|View full text |Cite
|
Sign up to set email alerts
|

The cocktail party problem: What is it? How can it be solved? And why should animal behaviorists study it?

Abstract: Animals often use acoustic signals to communicate in groups or social aggregations in which multiple individuals signal within a receiver's hearing range. Consequently, receivers face challenges related to acoustic interference and auditory masking that are not unlike the human "cocktail party problem," which refers to the problem of perceiving speech in noisy social settings. Understanding the sensory solutions to the cocktail party problem has been a goal of research on human hearing and speech communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
252
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(254 citation statements)
references
References 220 publications
(310 reference statements)
2
252
0
Order By: Relevance
“…Although we cannot conclude that the neurophysiological response properties we have described here are necessarily essential for behavior, several existing studies using synthetic stimuli (34) and speech (23) have demonstrated that ferrets and rodents are able to perceive target sounds in noisy conditions similar to those used in this study. The functional properties observed for speech and conspecific vocalizations in distorted conditions may reflect computational strategies used in these behaviors, and future studies that combine our unique computational approach and behavior paradigms promise valuable new insight into the general problem of identifying signals in the background of interfering sources (5). Although our focus in this study was to determine how different mechanisms contribute to the formation of the cortical representation under convolutive and additive distortions, a wider range of conditions is necessary to expand the findings and to determine how these mechanisms contribute to signal enhancement in various stationary, nonstationary, and, ultimately, competing vocalizations (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we cannot conclude that the neurophysiological response properties we have described here are necessarily essential for behavior, several existing studies using synthetic stimuli (34) and speech (23) have demonstrated that ferrets and rodents are able to perceive target sounds in noisy conditions similar to those used in this study. The functional properties observed for speech and conspecific vocalizations in distorted conditions may reflect computational strategies used in these behaviors, and future studies that combine our unique computational approach and behavior paradigms promise valuable new insight into the general problem of identifying signals in the background of interfering sources (5). Although our focus in this study was to determine how different mechanisms contribute to the formation of the cortical representation under convolutive and additive distortions, a wider range of conditions is necessary to expand the findings and to determine how these mechanisms contribute to signal enhancement in various stationary, nonstationary, and, ultimately, competing vocalizations (35).…”
Section: Discussionmentioning
confidence: 99%
“…Although substantial effort is required to perceive speech in extremely noisy conditions, accurate perception in moderately noisy and reverberant environments is relatively effortless (1), presumably because of the presence of general filtering mechanisms in the auditory pathway (2). These mechanisms likely influence the representation and perception of both speech and other natural sounds with similarly rich spectrotemporal structure, such as species-specific vocalizations (3)(4)(5). Despite the central role this robustness must play in animal and human hearing, little is known about the underlying neural mechanisms and whether the brain maintains invariant representations of these stimuli across variable soundscapes causing acoustic distortions of the original signals.…”
mentioning
confidence: 99%
“…Despite this difficulty, humans and other species can successfully listen and orient to individual sound sources, using a process termed auditory scene analysis (Bregman, 1990). Animal acoustic communication may suffer from similar problems (Bee and Micheyl, 2008), because background noise in choruses of calling individuals can be dramatic. In species-rich tropical rainforests, Ͼ50 species of insects and frogs create an acoustic background with vocalizations at high sound pressure levels (Römer et al, 2010;Schwartz and Bee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These constraints potentially act as sources of selection that can influence the evolution of how signals are designed (Boncoraglio and Saino, 2007;Ey and Fischer, 2009;Ryan and Kime, 2003), how signalers behave to produce signals in time and space (Brumm and Slabbekoorn, 2005;Ryan and Kime, 2003) and how the auditory systems of receivers extract biologically relevant signal properties (Bee and Micheyl, 2008;Brumm and Slabbekoorn, 2005;Langemann and Klump, 2005). In addition, receivers in some taxa can actually use the extent of degradation in acoustic signals to obtain information about the distance to signalers (Naguib and Wiley, 2001).…”
Section: Introductionmentioning
confidence: 99%